Treating Sexual Orientation Obsessive-Compulsive Disorder with Cognitive Analytic Therapy: Case Report and Quasi-Experimental Outcome Evaluation - Ese-Oghene Osivwemu; Melanie Simmonds-Buckley; Chris Gaskell; Stephen Kellett (Reports)
Background and Clinical Significance: Evaluations of interventions for sexual orientation obsessive–compulsive disorder (SO-OCD) are rare. This study therefore evaluated the effectiveness of cognitive analytic therapy (CAT). Case Presentation: A 28-year-old heterosexual male presented with SO-OCD in the form of obsessions concerning his sexual identity and associated avoidance and reassurance-seeking compulsions. The evaluation was a quasi-experiential A/B single-case experimental design (SCED) with follow-up of the eight-session CAT intervention. The SCED had three phases: baseline ‘A’ (two sessions; 21 days), active treatment ‘B’ (six sessions; 56 days) and follow-up (one session; 44 days). There were seven daily rated idiographic outcome measures (intrusion count as the control, a compulsion count and then intensity measures of checking, worrying, generating evidence, shame and anxiety). Four nomothetic outcome measures (including a primary outcome measure of SO-OCD) were collected at assessment, end of treatment and follow-up. Generalised logistical models were fitted to the idiographic outcomes. Six of the seven idiographic measures responded to treatment, indicating an effective intervention. Idiographic change was non-linear and synchronised with specific psychotherapeutic actions and there was no evidence of relapse. There was a clinically significant and reliable pre–post reduction in SO-OCD with progress sustained over the follow-up period. Conclusions: Overall, the study indicates that CAT was an effective intervention for the SO-OCD. The study methodology is critiqued and guidance on SO-OCD treatment is provided.